1976
DOI: 10.1039/c39760000485
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of bis-µ-(bisdiphenylphosphinomethane)-dibromodipalladium(Pd–Pd), a compound containing palladium(I)

Abstract: The crystal structure of [Pd(dppm) Br], (dppm = Ph,PCH,PPh2) shows that the palladium(1) atoms are directly metal-metal bonded and adopt an idealised square-planar stereochemistry.THE preparation of the complexes [Pd(dam)X], (dam = Ph,AsCH,AsPh,; X = C1, Br) and their establishment as compounds of palladium(1) was recently rep0rted.l By the action of dppm (Ph,PCH,PPh,) and the halogenocarbonyls Pd(C0)X we have now prepared similar complexes of the type [Pd(dppm)X], and the crystal structure of one o f these, [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…The torsion angle between the plane defined by {P(1), Pd(1), P(4) and Pd(2) atom} and {P(2), Pd(2), P(3) and Pd (1) atom} is 40.6˚, which is in the range of those (39 -50.5˚) in other dipalladium(I) dppm complexes. [7][8][9][10][11] In this study we also found another single crystal of [Pd 2 (m-dppm) 2 We thank Mr. Nobuhisa Shimada and Shin-ichi Akiyama for their assistances. This work was partially supported by a Grantin-Aid for Scientific Research from the Ministry of Education, Science and Culture, Japan.…”
mentioning
confidence: 77%
“…The torsion angle between the plane defined by {P(1), Pd(1), P(4) and Pd(2) atom} and {P(2), Pd(2), P(3) and Pd (1) atom} is 40.6˚, which is in the range of those (39 -50.5˚) in other dipalladium(I) dppm complexes. [7][8][9][10][11] In this study we also found another single crystal of [Pd 2 (m-dppm) 2 We thank Mr. Nobuhisa Shimada and Shin-ichi Akiyama for their assistances. This work was partially supported by a Grantin-Aid for Scientific Research from the Ministry of Education, Science and Culture, Japan.…”
mentioning
confidence: 77%
“…Pt(1)-Pt(2) [2.651 (1) A] is somewhat shorter than the Pd-Pd bond [2.699 (5) A] in the isomorphous and isostructural [{PdBr(#-dppm)} 2] analogue (Holloway, Penfold, Colton & McCormick, 1976). In the few other Pt i complexes examined so far the Pt-Pt distances are 2.581 (4)-2.647 (2) A (Brown, Puddephatt, Rashidi, Manojlovi6-Muir, Muir, Solomun & Seddon, 1977 (Modinos & Woodward, 1975).…”
Section: Bis-g-[bis(diphenylphosphino)methane]-bis(chloroplatinum)mentioning
confidence: 99%
“…2.212 A) and Pd-N (2.112 A) distances are close to those reported for the Pd-Rh, Pd-Ru, and Pd-Mo complexes. The Pd-P distances are significantly shorter than those of 2.29 A found in the P-P connecting ligand systems Pd,Br,(dpm), (31) and Pd,Cl,(dpmMe), (32); a similar shortening of the Rh-P bond in the A-frame, HT complex Rh,Cl,(PPh,py),(p.-CO) compared to dpm-bridged rhodium A-frame complexes has been rationalized in terms of the relative trans effects, P 2 N (30). The Pd-I bond lengths in 6c (2.696 and 2.695 A) are unusually long for terminal Pd-I bonds, but are essentially the same as found in the unbridged complex [PdI(MeNC),],, which contains a linear I-Pd; Pd-I unit with a metal-metal bond length of 2.533 A (33), and again the elongation is attributed to the trans effect of the Pd-Pd bond.…”
Section: Results and Discussion The Pdx2(pph3-npyn)2 Cornplexesmentioning
confidence: 82%